Penerapan program sekolah ramah anak di SDN 02 Sumberpasir Kecamatan Pakis Malang - Fitriati, Bunga; Rahmawati, Risa; Sonia, Chella; Sasongko, Dimas Femy (Maliki Interdisciplinary Journal, 2024)
The main principles of Sekolah Ramah Anak (SRA) are non-discriminatory interests, the right to life and respect for children. Bullying is an act of violence that is carried out both physically, psychologically, mentally and spiritually which can happen anywhere including the educational environment. PHBS is all health behavior that is carried out on self-awareness and plays an active role in health activities in the community. In the selected method through three stages, namely the pre stage, the implementation stage and the final stage. Pre-program stages consist of observation and interviews; the implementation phase consists of outreach regarding PHBS and Stop Bullying, posters affixing and implementation through community service, more intensive joint exercise, traditional games and complaint forums as well as simple counseling; the last stage of implementation consisted of distributing questionnaires to 30 samples which aimed to determine the level of understanding of a series of programs that had been implemented. High results were obtained from the questionnaire answered by the sample, this indicates that understanding of socialization is also high. From this research, it can be said that Sekolah Ramah Anak (SRA) have been implemented quite successfully, starting from the students’ understanding of SDN 02 Sumberpasir regarding PHBS and anti-bullying education, as well as significant implementation or implementation in the school environment.